Resposta astrocitária e oligodendroglial no tronco encefálico de ratos wistar imunossuprimidos e submetidos ao modelo desmielinizante do brometo de etídio - Sallis, Eliza Simone Viégas (2005)
Brain stem remyelination following demyelination induced by ethidium bromide (EB) is carried out by oligodendrocytes and Schwann cells that invade the central nervous system when astrocytes are lost. Although oligodendrocyte remyelination is detected from 13 days onward within the lesions, the origin of the remyelinating cells is not known. To clarify oligodendrocyte origin as well as to observe astrocytic behaviour in normal (n=22) as well as immunosuppressed animals (n=22) adult Wistar rats were injected with EB in the basal cisterna. Wistar rats had an EB injection while treated with cyclophosphamide (astrocyte investigation, n=12) or cyclosporine A (oligodendrocyte study, n=10). Control animals had a single injection of 10 μl of 0.9% saline (n=16). For the investigation on astrocytes, the rats were killed at 1, 2, 3, 7, 14 and 21 days a.i. GFAP labelled astrocytes were conspicuous within the lesions and isomorphic gliosis was detected, more marked in those rats immunosuppressed with CY. Nonetheless a significant difference among the groups could not be established because of the mean deviations detected by the image studies. For the oligodendrocyte investigation the rats were killed at 15, 21 and 31 days a.i. Lesions of EB injected in normal and cyclosporine A-treated Wistar rats labelled positive for OSP (oligodendrocytes specific protein). This result points to mature oligodendrocytes as a source of remyelinating cells to restore the lost myelin sheaths after EB injection. The EB model of demyelination allowed the observation of the neuroglia in lesions where remyelination is made up by mature cells of the oligodendroglial lineage and where astrocytes respond selectively to immunosuppressive drugs that modify the inflammatory reaction induced by EB